Education for self-reliance in Lesotho 1974-1990 - Tjabane, Masebala (My University, 1992)
Education for self-reliance in Lesotho is bound up with the educational developments in independent Africa that sought a more practical and relevant type of education as a solution to an overtly academic and western inclined education. This study examines Lesotho's experiences with education for self-reliance in the context of underdevelopment and dependence on the west and South Africa. The main argument of this study is that inadequate implementation procedures and methods tended to discredit the concept of education for self-reliance in Lesotho. However, the study demonstrates that with more appropriate principles and procedures, education for self-reliance could be an effective and viable option for minimising underdevelopment and dependence in Lesotho. In addition, this study argues that particular aspects of education for self-reliance such as development studies could encourage broad-based and collective development. For this purpose, lessons from Tanzania and Botswana are of crucial importance. The study draws on both primary and secondary sources. Primary sources include reports, official policy documents, oral evidence and official pamphlets on educational development in Lesotho. Secondary sources are a combination of books, journals and newspapers which cover topical issues on education and developments in Africa.
A research report submitted to the faculty of Education, University of the Witwatersrand, Johannesburg, in partial fulfilment of the degree of Master of Education
Keywords: Education -- Lesotho